Analisis Penerapan Model Pembelajaran Inkuiri Pada Mata Pelajaran IPA Materi Gerak Benda di Sekolah Dasar - Maulia Widya Prastiwi; Hanin Dewi Septiyaningtiyas; Nita Dwi Rahayu April; Fat-thahillah Candra At-Toriq; Wahyu Kurniawati (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This research aims to analyze the application of the inquiry learning model in science subjects regarding the movement of objects in elementary schools. This research used a literature study method which was carried out by reviewing 15 articles, consisting of 12 national journals and 3 international journals. The results obtained from this research are that science learning using the inquiry method on object movement material in elementary schools can be applied and based on the results of the review, science learning using the inquiry model will be more detailed and students will understand more easily, because students are directly involved in learning. the. So it can be concluded that 1) The inquiry learning model can be developed in all subjects, including science subjects which can involve children's ability to observe and research events. 2) The inquiry learning model in science (Natural Science) subjects can help make it easier for students to understand learning, especially regarding the movement of objects. 3) The inquiry learning model provides significant results on student learning outcomes in science subjects in elementary schools, so that in material on object movement, the inquiry learning model can be applied to achieve effective and efficient learning.